2019
DOI: 10.3390/polym11111763
|View full text |Cite
|
Sign up to set email alerts
|

Surface Treatment Effects on the Mechanical Properties of Silica Carbon Black Reinforced Natural Rubber/Butadiene Rubber Composites

Abstract: For the first time, phenolic formaldehyde resin (PF)-treated silica carbon black (SiCB) were prepared with different treatment conditions and their effect as fillers on the mechanical properties of filler filled natural rubber/butadiene rubber (NR/BR) composites were investigated in detail. The PF coating layer on the SiCB derived from rusk husk not only promoted the dispersion of the fillers but also improved the interfacial interactions between fillers and the rubber matrix. As a result, both the cross-link … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 43 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…From the FE-SEM micrographs (Figure 4), it is found that all vegetable oils used in this work give similar degree of filler dispersion. Compared with NTO, both MO and NO give smaller size of silica agglomerates and, thus, provide better silica dispersion which leads to the significant improvements in the mechanical and dynamic properties [27][28][29][30].…”
Section: Effect Of Oils On Morphology and Storage Modulusmentioning
confidence: 99%
“…From the FE-SEM micrographs (Figure 4), it is found that all vegetable oils used in this work give similar degree of filler dispersion. Compared with NTO, both MO and NO give smaller size of silica agglomerates and, thus, provide better silica dispersion which leads to the significant improvements in the mechanical and dynamic properties [27][28][29][30].…”
Section: Effect Of Oils On Morphology and Storage Modulusmentioning
confidence: 99%
“…Mechanical properties of NR/BR materials are shown in Table S2 . The elastomer composites were prepared using a laboratory-sized internal mixer (KY-3220C-1L, Dongguan Kaiyan Machinery Equipment Factory, Dongguan, China) according to the formulations listed in previous work [ 35 ]. NR and MA were first mixed in an internal mixer at 40 rpm and 100 °C for 10 min to incorporate MA onto the main chain of NR.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments by Kaewsakul et al [ 41 ] show that chemically bonded rubber contents plateau once silane content in coupling agents approach 10 wt %. Other approaches to improve silica compatibility with rubber include functionalizing rubber compounds with polar groups [ 42 , 43 ], modification of silica surface through grafting [ 44 ], combining it with CB [ 45 ], making hybrid fillers with graphene nanoplatelets [ 46 ] and synthesizing novel silica with high dispersity [ 47 ].…”
Section: Conventional Rubber Fillers For Mechanical Reinforcementmentioning
confidence: 99%